2020
DOI: 10.1002/hipo.23191
|View full text |Cite
|
Sign up to set email alerts
|

Untethered firing fields and intermittent silences: Why grid‐cell discharge is so variable

Abstract: Grid cells in medial entorhinal cortex are notoriously variable in their responses, despite the striking hexagonal arrangement of their spatial firing fields. Indeed, when the animal moves through a firing field, grid cells often fire much more vigorously than predicted or do not fire at all. The source of this trial‐to‐trial variability is not completely understood. By analyzing grid‐cell spike trains from mice running in open arenas and on linear tracks, we characterize the phenomenon of “missed” firing fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…Indeed, the findings of a hippocampus-wide (Figs. 6, 7), DS M -promoted SG dom control of hippocampus information processing to a non-local mode of information processing identify a source of the overdispersion that is characteristic of place cells in CA1, CA3, and DG (Fenton et al, 2010; Fenton and Muller, 1998; Hok et al, 2012; Jackson and Redish, 2007; van Dijk and Fenton, 2018), and also grid cells, although we cannot conclude the mechanism is the same (Nagele et al, 2020). The findings also offer an explanation for the possible utility of CA1 receiving two spatial inputs; the Schaffer collaterals provide place cell inputs that can be non-local and related to mental experience, whereas the temporoammonic pathway provides an input comprised of components of place (grid cell distances, directional cells, border cells, and speed cells) more tethered to local, physical experience.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the findings of a hippocampus-wide (Figs. 6, 7), DS M -promoted SG dom control of hippocampus information processing to a non-local mode of information processing identify a source of the overdispersion that is characteristic of place cells in CA1, CA3, and DG (Fenton et al, 2010; Fenton and Muller, 1998; Hok et al, 2012; Jackson and Redish, 2007; van Dijk and Fenton, 2018), and also grid cells, although we cannot conclude the mechanism is the same (Nagele et al, 2020). The findings also offer an explanation for the possible utility of CA1 receiving two spatial inputs; the Schaffer collaterals provide place cell inputs that can be non-local and related to mental experience, whereas the temporoammonic pathway provides an input comprised of components of place (grid cell distances, directional cells, border cells, and speed cells) more tethered to local, physical experience.…”
Section: Discussionmentioning
confidence: 97%
“…This irregularity is also seen in continual neural recordings without trial structure [8]. The resulting variability has classically been characterised as ‘Poisson’, with a Fano factor (variance to mean ratio) of one [9], but experimental data also often exhibits significantly more [10, 8, 11, 12] and sometimes less [13, 14] variability, respectively referred to as over- or underdispersion. Moreover, experimental studies have revealed that neural variability generally depends on stimulus input and behaviour [15, 16, 17, 18], and exhibits structured shared variability (‘noise correlations’) across neurons even after conditioning on such covariates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent models have computed the successor representation between different spatial locations laid out as a discrete array of locations, showing how the eigenvectors of these successor representations can appear similar to grid cells (Stachenfeld, Botvinick, & Gershman, 2017). This provides another framework for addressing the firing properties of grid cells, which have been addressed in other papers in this special issue (Bush & Burgess, 2020; Nagele, Herz, & Stemmler, 2020; Stella et al, 2020). However, the discretization of an array of locations does not easily address the effect of changes in the shape and size of the environment or the position of barriers (Barry, Hayman, Burgess, & Jeffery, 2007; Burgess & O'Keefe, 1996), or the role of spatial context (Zhu, Paschalidis, Chang, Stern, & Hasselmo, 2020).…”
Section: Data Support Role In Planning Of Spatial Navigationmentioning
confidence: 96%